Geospatial services and applications for the Internet - Sample, John T. (Springer, 2017)
"Geospatial Services and Applications for the Internet covers a wide spectrum of techniques, algorithms and modeling methodologies that address the challenges in service-oriented architectural design for GIS, and intelligent processing for spatial queries. This book presents in-depth studies on performance improvement, data integration, service personalization and interoperation between geospatial services. These studies provide the reader with a wide spectrum of examples and case studies on the development of GIS for hydrological applications, electrical power supply applications, land usage and urban planning, and NASA's Earth image datasets dissemination." "Geospatial Services and Applications for the Internet is designed for a professional audience composed of practitioners and researchers in industry. This book is also suitable as a secondary textbook or reference for advanced-level students in computer science and geosciences."--BOOK JACKET.